ERATOSTHENES: Excellence research Centre for Earth surveillance and space-based monitoring of the environment, the EXCELSIOR Horizon 2020 teaming project - Hadjimitsis, Diofantos G.; Kontoes, Haris; Schreier, Gunter; Ansmann, Albert; Komodromos, George; Themistocleous, Kyriacos; Mamouri, Rodanthi-Elisavet; Michaelides, Silas; Nisantzi, Argyro; Papoutsa, Christiana; Neocleous, Kyriacos; Mettas, Christodoulos; et al. (My University, 2017)
The aim of this paper is to present the strategy and vision to upgrade the existing ERATOSTHENES Research Centre (ERC) established within the Cyprus University of Technology (CUT) into a sustainable, viable and autonomous Centre of Excellence (CoE) for Earth Surveillance and Space-Based Monitoring of the Environment, which will provide the highest quality of related services on the National, European and International levels. EXCELSIOR is a Horizon 2020 Teaming project which addresses a specific challenge defined by the work program, namely, the reduction of substantial disparities in the European Union by supporting research and innovation activities and systems in low performing countries. It also aims at establishing long-term and strategic partnerships between the Teaming partners, thus reducing internal research and innovation disparities within European Research and Innovation landscape. The proposed CoE envisions the upgrading of the existing ERC into an inspiring environment for conducting basic and applied research and innovation in the areas of the integrated use of remote sensing and space-based techniques for monitoring the environment. Environment has been recognized by the Smart Specialization Strategy of Cyprus as the first horizontal priority for future growth of the island. The foreseen upgrade will regard the expansion of this vision to systematic monitoring of the environment using Earth Observation, space and ground based integrated technologies. Such an approach will lead to the systematic monitoring of all three domains of the Environment (Air, Land, Water). Five partners have united to upgrade the existing ERC into a CoE, with the common vision to become a world-class innovation, research and education centre, actively contributing to the European Research Area (ERA). More specifically, the Teaming project is a team effort between the Cyprus University of Technology (CUT, acting as the coordinator), the German Aerospace Centre (DLR), the National Observatory of Athens (NOA), the German Leibniz Institute for Tropospheric Research (TROPOS) and the Cyprus Department of Electronic Communications of the Ministry of Transport, Communications and Works (DEC-MTCW).
Keywords: Centre of Excellence; Cyprus; Environmental monitoring; Remote sensing; Smart Specialization Strategy